2014
DOI: 10.6061/clinics/2014(01)05
|View full text |Cite
|
Sign up to set email alerts
|

The thickness of posterior cortical areas is related to executive dysfunction in Alzheimer's disease

Abstract: OBJECTIVE:To establish whether alterations of brain structures in Alzheimer's disease are associated with executive dysfunction.METHODS:Nineteen patients with Alzheimer's disease and 22 older control subjects underwent a comprehensive evaluation. The clock drawing test, digit span test, executive motor function test, Behavioral Assessment of the Dysexecutive Syndrome battery (Rule Shift Cards test), and Stroop test were used to evaluate executive dysfunction. A multiparametric approach using the FreeSurfer ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
(60 reference statements)
3
14
0
4
Order By: Relevance
“…The isthmus cingulate, which connects the cingulate gyrus to the parahippocampal gyrus, was significantly reduced in ε 4 carriers and in male ε 4 carriers relative to ε 4 non-carriers and male ε 4 non-carriers, respectively ( Sener,1997 ). This finding is supported by previous literature reporting greater atrophy and increased rate of cortical thinning in the isthmus cingulate in AD ( Hayata et al, 2015 ; Mak et al, 2015 ; Vasconcelos et al, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…The isthmus cingulate, which connects the cingulate gyrus to the parahippocampal gyrus, was significantly reduced in ε 4 carriers and in male ε 4 carriers relative to ε 4 non-carriers and male ε 4 non-carriers, respectively ( Sener,1997 ). This finding is supported by previous literature reporting greater atrophy and increased rate of cortical thinning in the isthmus cingulate in AD ( Hayata et al, 2015 ; Mak et al, 2015 ; Vasconcelos et al, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, our results showed that the poor performance on the Stroop test was related to not only cortical thinning of prefrontal cortex, but also the thinning of parieto-temporal areas, different from results of prior studies. Luciano has also shown that right superior parietal gyrus and middle temporal gyrus are correlated negatively with scores of the Stroop test in patients with AD 61. In fact, previous studies using different neuroimaging methods have correlated parietal and temporal structures with executive functions 6263.…”
Section: Discussionmentioning
confidence: 93%
“…Posterior cingulated cortex (PCC) [ 24 ], entorhinal cortex (EC) [ 25 ], hippocampus (HIP) [ 26 ] (the first part to be affected by AD), middle temporal gyrus (MTG) (role in cognitive functions such as language processing), and superior frontal gyrus (SFG) (helps in memory) [ 27 , 28 ] are the regions affected in this multifactorial neurological disorder. Some studies have identified the impaired function of the middle temporal gyrus [ 29 ] and superior frontal gyrus in AD [ 30 ].…”
Section: Introductionmentioning
confidence: 99%